STRATEGI APLIKASI SEL SURYA (PHOTOVOLTAIC CELLS) PADA PERUMAHAN DAN BANGUNAN KOMERSIAL - Danny Santoso Mintorogo (DIMENSI (Journal of Architecture and Built Environment), 2000)
World Oil Energy crisis in the Europe and West countries that forces them to look for alternative energy in term of innovation of photovoltaics technology. Photovoltaics Energy that is so clean, it causes zero pollution and so simple to apply that you hardly know it sit there, no sound and noise, no smoke, no CO2 and Nitrogen-just pure power. That imaginarily nice communities is here now. The communities, countries, and worlds are Solar. The photovoltaic technology has reached to both the invention of the solar cell materials, and to the application of highly applied solar cells technologies in term of building materials such as roofings, claddings-curtain walls and curtain glasses,as well as architectural atria and canopy. Abstract in Bahasa Indonesia : Krisis energi dunia dan tingginya harga sumber energi (minyak) di belahan dunia Eropa dan Barat menyebabkan innovasi dalam pemanfaatan energi alternatif yang tidak menimbulkan polusi udara CO2 maupun radioaktif (nuclear power). Energi Sel Surya adalah jawaban tepat dalam menciptakan suatu lingkungan hidup dalam lingkup perumahan maupun bangunan komersial yang ramah lingkungan, abadi, dan gratis dalam tata surya kita ini. Teknologi Aplikasi Sel Surya terus dikembangkan baik dalam innovasi chip sel surya sendiri maupun aplikasi pada bangunan arsitektur dalam berbagai material bangunan seperti : bahan atap, penutup facade bangunan ( cladding dan curtain wall atau glass ), canopy atau atrium. Kata kunci: sel surya, perumahan, bangunan komersial.